2018
DOI: 10.1007/s11906-018-0881-z
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Oral Taurine on Resting Blood Pressure in Humans: a Meta-Analysis

Abstract: There is growing evidence that taurine deficiency is associated with hypertension and that oral supplementation can have antihypertensive effects in humans. However, these investigations have been conducted across a number of decades and populations and have not been collectively reviewed. A search was performed using various databases in May 2018 and later screened using search criteria for eligibility. There were seven peer-reviewed studies meeting the inclusion criteria, encompassing 103 participants of var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 56 publications
0
28
0
1
Order By: Relevance
“…Therefore, an adult weighing 70 kg would require a dose of 3.5 g 1.5-2 h before training or competition to achieve an ergogenic effect. There have been no adverse side-effects reported across studies using doses up to 6 g (Waldron et al 2018c), inferring the safety and tolerability of this supplement. The effects of taurine on endurance performance are fairly well-established among recreational athletes but, to date, there has been no work carried out on elite-level athletes, which is necessary to develop an understanding of the scope of taurine's ergogenic effects.…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, an adult weighing 70 kg would require a dose of 3.5 g 1.5-2 h before training or competition to achieve an ergogenic effect. There have been no adverse side-effects reported across studies using doses up to 6 g (Waldron et al 2018c), inferring the safety and tolerability of this supplement. The effects of taurine on endurance performance are fairly well-established among recreational athletes but, to date, there has been no work carried out on elite-level athletes, which is necessary to develop an understanding of the scope of taurine's ergogenic effects.…”
Section: Discussionmentioning
confidence: 80%
“…The increased level of glutamine may be related to the increased hydroxyproline because it is the precursor of the proline biosynthesis, an essential element of collagen. Interestingly, four of these amino acids or biogenic amines have already been reported to display antihypertensive properties, as demonstrated for histidine through central histamine H3 receptors and decreased NO 49 , for tyrosine through the effect of its product, norepinephrine, on the central nervous system 50 , for phenylalanine through GTP cyclohydrolase inhibition 51 , and for taurine 52 . These discriminant metabolites may represent protective mechanisms to counteract increased blood pressure in women.…”
Section: Discussionmentioning
confidence: 99%
“…Taurine deficiency was reported to induce several diseases in animal models including retinal degeneration (Negoro and Hara 1992;Ripps and Shen 2012), dilated cardiomyopathy (Lake 1992;Pion et al 1992;Novotny and Hogan 1992;Schaffer and Kim 2018), deficiency of immune functions (Negoro and Hara 1992;Lake et al 1992), hypertension (Waldron et al 2018;Schaffer and Kim 2018), and aging (Schaffer et al 2015;Ames 2018). For example, in humans, higher incidences of development of hypertension (Xu et al 2008;Waldron et al 2018) as well as cardiac diseases (Azuma 1989;Xu et al 2008) were reported in populations having low-taurine diets (Yamori et al 2004;Sagara et al 2015;Schaffer and Kim 2018). Recently, taurine transporter (Taut) knockout mice were used to understand the effects of taurine tissue depletion.…”
Section: Taurine Deficiencymentioning
confidence: 99%